Digital-Game Based Learning Innovation on POE: Constructing Student’s Mental Models on Temperature Effect on Reaction Rate - Finny Rahmatania; Wiji Wiji; Sri Mulyani (Jurnal Penelitian Pendidikan IPA, 2024)
The aim of this study is to identify how the POE learning integrated into D-GBL can construct student’s mental models on temperature effect on reaction rate and the game design is created. This research is a part of the Research and Development (R&D) with Borg and Gall model. This study is focused on the third stage. The study began with collecting information, planning product, and prototype development. For product design, the study created mission and sub-missions to represent the POE steps, which are predicting, observing, and explaining. The information was collected from various literature reviews on D-GBL and mental model. For product design, mission and sub-missions were created to represent POE steps. Next, the prototype was developed in the form of a game design document. Students must answer various questions to complete these missions and sub-missions. If the answers are given incorrect, the game restart from the beginning of that mission. Therefore, D-GBL integrated in the POE model can construct students' mental models.